Effects of Transcranial Pulse Stimulation (TPS) on Young Adults With Symptom of Depression: A Pilot Randomised Controlled Trial Protocol - Cheung, Teris; Ho, Yuen Shan; Yeung, Jerry Wing-Fai; Leung, Sau Fong; Fong, Kenneth N. K.; Fong, Tommy; Kranz, Georg S.; Beisteiner, Roland; Cheng, Calvin Pak Wing (Frontiers in Neurology, 2022)
Background: Since the emergence of COVID-19 pandemic, there have been lots of published work examining the association between COVID19 and mental health, particularly, anxiety and depression in the general populations and disease subpopulations globally. Depression is a debilitating disorder affecting individuals’ level of bio-psychological-social functioning across different age group. Nonetheless, almost all studies were cross-sectional studies, there seems to be a lack of robust, large-scale and technological-based interventional studies to restore the general public’s optimal psychosocial wellbeing amidst COVID-19 pandemic. Transcranial Pulse Stimulation (TPS) is a relatively new NIBS technology, There is no study conducted on young adults with major depressive disorder nationwide. This gives us the impetus to execute the first nationwide study evaluating the efficacy of TPS on treatment of depression among young adults in Hong Kong. Methods: This is a two-armed single-blinded randomized controlled trial including TPS as an intervention group and a waitlist control group. Both groups will be measured at baseline (T1), immediately after the intervention (T2) and at the 3- month follow-up (T3). Recruitment: A total of 30 community dwelling subjects, aged 18 and above, diagnosed with major depressive disorder (MDD), will be recruited. All subjects will be computer randomized into either the intervention group or the waitlist control group, balanced by gender, and age, on a 1: 1 ratio. Intervention: All subjects in each group will have to undertake fMRI before, and after six 30- minutes TPS sessions, which will be completed in two weeks’ time. Outcomes: Baseline measurements and post-TPS evaluation of the psychological outcomes (i.e., depression, cognition, anhedonia, instrumental activities of daily living) will also be conducted on all participants. A 3-month follow-up period will be used to assess the long-term sustainability of the TPS intervention. Statistical analysis: ANOVA with repeated measures will be used to analyze data. Missing data will be managed by multiple mutation. Level of significance will be set at p< 0.05. Significance of the study: Results will inform health policy to determine whether TPS can be considered as a top on treatment option for MDD. This trial is registered with Clinical Trial Registry, identifier: NCT05006365